Innovative Clinical Pathways for Pregnant Women with Obesity: The Padua Project (Northeastern Italy) - Maria Grazia Dalfrà; Giovanni Sartore; Eugenio Ragazzi; Silvia Burlina; Silvia Visentin; Silvia Pastrolin; Marco Tosi; Erich Cosmi; Annunziata Lapolla (Journal of Clinical Medicine, 2026)
Background/Objectives: Maternal obesity is associated with an increased risk of adverse maternal and neonatal outcomes. This study evaluated whether participation in a multidisciplinary antenatal care pathway improved pregnancy outcomes compared with routine clinical practice in women with pre-pregnancy obesity. Methods: 711 women of reproductive age with preconception body mass index (BMI) ≥ 30 kg/m2 were identified from medical records collected between 2010 and 2023: 233 women were managed according to the multidisciplinary clinical pathway (pathway group), and 478 served as historical controls, followed at the same unit before pathway implementation. Age, BMI, gestational diabetes frequency, weight gain during pregnancy, gestational hypertension, preeclampsia/eclampsia, time and mode of delivery, birthweight, macrosomia, large for gestational age, neonatal hypoglycemia, hyperbilirubinemia, respiratory distress, fetal morbidity, and congenital anomalies were collected. Fasting plasma glucose, glycated hemoglobin, plasma glucose values under oral glucose tolerance test, plasma cholesterol and triglyceride levels were also evaluated. Results: The first evaluation occurred significantly earlier in the pathway group than in controls. Only about half of the women in the pathway group developed gestational diabetes mellitus (GDM) during pregnancy compared with 84% of controls (47% vs. 84%, p < 0.001), a difference partly explained by a referral bias in the control group, where women were referred after GDM screening rather than on the basis of obesity alone. As for maternal complications, the frequency of hypertension, eclampsia, and preeclampsia was similar in the two groups. As for fetal outcomes, pathway group women with respect to control showed a significantly lower frequency of preterm birth (5% vs. 11%, p = 0.0275), fetal morbidity (2% vs. 6%, p = 0.0377) and a tendency to lower frequency of macrosomia (7% vs. 12%, p = 0.0677), large for gestational age (19% vs. 26%, p = 0.116) and small for gestational age babies (5% vs. 7%, p = 0.50). Conclusions: This study shows that a multidisciplinary antenatal clinical approach was associated with a reduction in some adverse maternal–fetal outcomes related to pregnancy complicated by obesity, despite a less favorable baseline risk profile in the pathway group. Preconception counseling starting before pregnancy may represent an even more effective strategy, and efforts must be made in this direction.